(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Brass Alloy 260 is widely used in mechanical engineering (odometer contacts, radiator cores), electrical engineering (electrical connectors, screw shells), plumbing (bathroom fixtures), consumers (watch parts, buttons, lamps) etc. The paper presents an analysis of the laser marking and engraving process. The ability Rofin powerline f20 laser system to engrave on Brass Alloy 260 is described. Recommendations are given on choosing the right parameters for laser marking and engraving of Brass Alloy 260 products.